Gas turbine part protective coating material and preparation method thereof

By using boron-doped TiHfTa medium entropy alloy and laser cladding technology to prepare the coating, and performing precision rolling and aging heat treatment, the problem of insufficient protective performance of the existing coating under high-parameter operating conditions is solved, and the high-temperature oxidation resistance and wear resistance of the coating are significantly improved.

CN119553271APending Publication Date: 2025-03-04SICHUAN UNIV

Patent Information

Application Number
CN202411882533.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The protective performance of existing carbide-based cermet coatings still needs to be improved under high-parameter operating conditions, especially in terms of strength, hardness, wear resistance, plastic toughness and high temperature resistance.

Method used

Boron-doped TiHfTa medium entropy alloy is used as the bonding phase of the WC-based coating, and the coating is prepared by laser cladding, and precision rolling processing and aging heat treatment are carried out to form Ti-B, Hf-B, Ta-B complexes and W2Co21B6 phases to improve the coating's high temperature oxidation resistance and wear resistance.

Benefits of technology

It significantly improves the high temperature oxidation resistance and wear resistance of the coating, and meets the protection requirements under high-parameter operating conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

The invention discloses a gas turbine part protective coating material and a preparation method thereof, and is characterized in that a boron-doped TiHfTa medium entropy alloy is used as a binding phase of a WC-based coating, a coating prepared by laser cladding is subjected to precise rolling processing and aging heat treatment to form Ti-B, Hf-B and Ta-B complexes, and the complexes are subjected to heat treatment to form a WC-based coating. The W2Co21B6 phase and the hBN have an improvement effect on the high-temperature wear resistance, the oxidation resistance and the like of the coating. The problem that a coating prepared in the prior art is insufficient in protection performance is solved, and the coating can be used for protection of key parts of the gas turbine.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a coating material and a preparation method thereof, and in particular to a gas turbine component protective coating material and a preparation method thereof, and belongs to the fields of high-end equipment manufacturing, new materials, surface engineering and clean energy. Background Art

[0002] Gas turbines are known as the pearls of industry. They use continuous flowing gas as the working fluid to drive the impeller to rotate at high speed, converting the energy of the fuel into useful work. They are typical high-end equipment. Most of the key components of gas turbines serve in harsh working conditions and have high requirements for high temperature resistance and wear resistance. Therefore, surface coating treatment is required in the project to protect key components and increase their service life.

[0003] CN112760540A discloses a composite WC-CrC-CoCr thermal spray powder and a preparation method thereof, comprising: (1) mixing tungsten trioxide, chromium trioxide, tungsten carbide, cobalt powder, carbon black, water and a binder and ball milling to obtain a ball milling slurry; (2) drying and atomizing the ball milling slurry to obtain spherical particles; (3) sintering the spherical particles under a protective atmosphere containing nitrogen and hydrogen to obtain a sintered material; (4) crushing the sintered material and classifying it to obtain a composite WC-CrC-CoCr thermal spray powder. The preparation method has a simple process, the two raw materials are moved to the oxide, the cost is low and it is suitable for industrial production, and the preparation process can effectively avoid gaseous carbon sources, and the carbon amount can be fine-tuned by the atmosphere, the process is green and safe, and the prepared composite WC-CrC-CoCr thermal spray powder has good toughness, and has good wear resistance, density and corrosion resistance. CN101613860A discloses a laser hard surface coating process for a gas turbine titanium alloy blade. According to the geometric shape of the blade tip or damping shoulder structure, a corresponding sleeve mold is used, and powder is pre-placed in the sleeve mold. The powder is a composite powder mixed with titanium alloy powder and metal carbide powder or B4C powder or BN powder. The sleeve mold and the powder added therein form a static powder bed, and the powder is pre-placed uniformly on the blade tip or blade damping shoulder by using the static powder bed; an inert gas or N2 is used to protect the laser irradiation area, and the blade is laser irradiated. The present invention can form a hard surface coating with a hardness of 35 to 62 HRC and a thickness of 0.05 to 2.0 mm on the blade tip or damping shoulder of the titanium alloy blade.

[0004] At present, carbide-based metal ceramic coatings have been widely used in the protection of many parts, but the mechanical properties such as strength, hardness, wear resistance, plasticity and toughness and high temperature resistance of the coating materials still need to be further improved to meet the protection requirements in high-parameter working conditions. Summary of the invention

[0005] The present invention aims to provide a gas turbine component protective coating material and a preparation method thereof. The present invention uses a boron-doped TiHfTa medium entropy alloy as a binder phase of a WC-based coating. The coating prepared by laser cladding is subjected to precision rolling and aging heat treatment to form a Ti-B, Hf-B, Ta-B complex, and W2Co 21 B6 phase and hBN can improve the high temperature wear resistance and oxidation resistance of the coating.

[0006] The gas turbine component protective coating material of the present invention is characterized in that the composition is 4-10% by weight of boron-doped TiHfTa medium entropy alloy, 5-10% by weight of Co, and the rest is WC; the molar ratio of Ti:Hf:Ta in the boron-doped TiHfTa medium entropy alloy is 1:1:1, and the boron content is 0.5-1.0 at.%; the coating phase composition is WC+Co+hBN+W2Co 21 TiHfTaB with B6+BCC structure has a 15~30μm plastic deformation layer on its surface. In the plastic deformation layer, there are short-range ordered Ti-B, Hf-B, and Ta-B complexes with a size of 1~5nm in TiHfTaB, and the B atoms are in the tetrahedral gaps of the TiHfTaB lattice.

[0007] The method for preparing the protective coating material for gas turbine components of the present invention is characterized by comprising the following steps in sequence: (1) Preparation of boron-doped TiHfTa medium-entropy alloy powder: Ti, Hf and Ta powders were weighed in a molar ratio of 1:1:1 and put into a planetary ball mill for 72-96 h. After filtering and spray drying, spherical powders with a particle size of 20-30 μm were obtained. The spherical powders were pressed into green bodies with a thickness of 0.5-1 mm and a density of 52-56%. The boron-containing medium was first loaded into a ceramic crucible with a lid. The composition of the boron-containing medium was 10-20 wt.% of B4C, 10-20 wt.% of KBF4, 5-10 wt.% of LaF3, and the rest was SiC. The mixture was kept at 900-1000 °C in an argon atmosphere for 2-3 h. After crushing and sieving, TiHfTa medium-entropy alloy powders with a boron content of 0.5-1.0 at.% were prepared. (2) Preparation of hBN dispersion: Nano-hBN and Tween 80 were added to anhydrous ethanol to form a mixed solution, in which nano-hBN accounted for 1-2 mol / L and Tween 80 accounted for 0.1-0.5 mol / L. After ultrasonic dispersion and pH adjustment, the Zeta potential was adjusted to 30-40 mV, and the hBN dispersion was prepared. (3) Preparation of protective coating powder: Weigh raw material powders by weight, wherein entropy alloy powder accounts for 4-10% of boron-doped TiHfTa, Co accounts for 5-10%, and the rest is WC powder; ball-mill the weighed raw material powders for 10-20 hours, filter and spray-dry, and then vacuum sinter at 1150-1250°C for 1-2 hours to prepare porous spherical composite powders; immerse the spherical composite powders in a hBN dispersion system, wherein the molar ratio of hBN to Co in the spherical composite powders is (1-2):10, and place the spherical composite powders in a vacuum drying oven for vacuum adsorption and drying treatment, with a vacuum degree of ≤200Pa, so that the composite sol is completely adsorbed into the pores of the agglomerates, to prepare protective coating powders with an average particle size of 30-45 μm and a composition of WC+Co+hBN+BCC structured TiHfTaB; (4) Preparation of coating by laser cladding: The metal substrate is kept at 100-150°C for 30-60 min, and the prepared high temperature resistant, oxidation resistant and wear resistant coating powder is used to prepare the laser cladding coating on the surface of the metal substrate by synchronous powder feeding. The laser power is 600-1000 W, the spot diameter is 2-4 mm, the powder feeding speed is 10-15 g / min, the scanning speed is 1-3 mm / s, and the overlap rate is 30-40%. The prepared phase composition is WC+Co+hBN+W2Co 21 Coating composed of TiHfTaB with B6+BCC structure; (5) Precision rolling of coating: The coating surface is rolled using a single crystal diamond ball head tool. The machine speed is 200-300 r / min, the feed rate is 0.01-0.04 mm / r, the curvature radius of the diamond ball head is 1.0 mm, and a plastic deformation layer with a thickness of 15-30 μm is formed on the surface of the coating. The dislocation density in the plastic deformation layer is 6×10 8 ~3×10 9 mm -2 , porosity 0.05~0.1%, the phase of the plastic layer remains unchanged; (6) Aging heat treatment of the coating: The rolled coating is heated to 700-780°C in a vacuum, kept at this temperature for 3-5 hours, and then cooled in the furnace. Short-range ordered Ti-B, Hf-B, and Ta-B complexes with a size of 1-5 nm are formed in the TiHfTaB in the plastic deformation layer on the coating surface, and the B atoms are located in the tetrahedral gaps of the TiHfTaB lattice.

[0008] The method for preparing the protective coating material for gas turbine components of the present invention is further characterized by: (1) When preparing boron-doped TiHfTa medium entropy alloy powder, the weight ratio of the boronizing medium to the green body is 4:1, and the thickness of the boronizing agent filled between the green body and the crucible wall after the green body is buried is greater than 4 mm; (2) When preparing the hBN dispersion system, after ultrasonic dispersion treatment for 30-60 min, the pH value was adjusted to 8-9 with ammonia water; (3) When preparing high temperature resistant, oxidation resistant and wear resistant coating powder, the vacuum adsorption and drying process is first kept at 50~60℃ for 1~2h, and then dried at 110~120℃ for 2~3h; (4) When laser cladding is used to prepare the coating, the flow rate of high-purity argon gas is 1~2L / min; (5) During precision rolling of the coating, the angle between the axis of the diamond indenter and the normal of the coating surface is 45°; (6) During the aging heat treatment of the coating, the heating rate is 5°C / min and the initial vacuum degree is 5~10Pa.

[0009] The advantages of the present invention are: (1) TiHfTaB high entropy alloy has a good strengthening effect on the coating and can improve the high temperature resistance and oxidation resistance of the coating. (2) hBN is evenly dispersed and has a low friction coefficient at high temperature, which can reduce wear. (3) W2Co formed by hBN, WC and Co 21 B6 phase can strengthen the bonding phase and improve wear resistance; (4) The formation of short-range ordered complexes of Ti-B, Hf-B, and Ta-B can strengthen the coating and improve the wear resistance, heat resistance, and oxidation resistance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 Schematic diagram of the method for preparing the protective coating material for gas turbine components of the present invention. DETAILED DESCRIPTION

[0011] Example 1: The composition of the protective coating material for gas turbine components is 5% boron-doped TiHfTa medium entropy alloy, 6% Co, and the rest WC by weight percentage; the molar ratio of Ti:Hf:Ta in the boron-doped TiHfTa medium entropy alloy is 1:1:1, and the boron content is 0.6at.%; the coating phase composition is WC+Co+hBN+W2Co 21 TiHfTaB with B6+BCC structure has a 16μm plastic deformation layer on its surface. In the plastic deformation layer, there are short-range ordered Ti-B, Hf-B, and Ta-B complexes with a size of 2 nm in TiHfTaB, and the B atoms are in the tetrahedral gaps of the TiHfTaB lattice.

[0012] The preparation method of the protective coating material for gas turbine components is as follows: (1) Preparation of boron-doped TiHfTa medium-entropy alloy powder: Ti, Hf and Ta powders were weighed in a molar ratio of 1:1:1, and put into a planetary ball mill for 72 hours. After filtering and spray drying, spherical powders with a particle size of 22 μm were obtained. The spherical powders were pressed into green bodies with a thickness of 0.5 mm and a density of 52%. First, a boronizing medium was loaded into a ceramic crucible with a lid. The composition of the boronizing medium was B4C accounting for 12 wt.%, KBF4 accounting for 10 wt.%, LaF3 accounting for 6 wt.%, and the rest was SiC. The weight ratio of the boronizing medium to the green body was 4:1. After the green body was buried, the thickness of the boronizing agent filled between the crucible wall was 5 mm. The mixture was kept at 900 °C in an argon atmosphere for 2 hours, and after crushing and sieving, a TiHfTa medium-entropy alloy powder containing 0.6 at.% boron was prepared. (2) Preparation of hBN dispersion: Nano-hBN and Tween 80 were added to anhydrous ethanol to form a mixed solution, in which nano-hBN accounted for 1 mol / L and Tween 80 accounted for 0.2 mol / L. After ultrasonic dispersion treatment for 30 min, the pH value was adjusted to 8 with ammonia water and the Zeta potential was 31 mV, thus preparing the hBN dispersion. (3) Preparation of protective coating powder: Weigh the raw material powder according to the weight percentage, wherein the entropy alloy powder of boron-doped TiHfTa accounts for 5%, Co accounts for 6%, and the rest is WC powder; ball-mill the weighed raw material powder for 12 hours, filter and spray-dry, and then vacuum sinter at 1150°C for 1 hour to prepare a porous spherical composite powder; immerse the spherical composite powder in an hBN dispersion system, wherein the molar ratio of hBN to Co in the spherical composite powder is 1:10, and place it in a vacuum drying oven for vacuum adsorption and drying treatment, the vacuum degree is 180Pa, and the vacuum adsorption and drying treatment is first kept at 50°C for 1 hour, and then dried at 110°C for 2 hours, so that the composite sol is completely adsorbed into the pores of the agglomerate, and a protective coating powder is prepared, the average particle size is 34μm, and its composition is WC+Co+hBN+BCC structure TiHfTaB; (4) Laser cladding coating preparation: The metal substrate was kept at 110°C for 30 min, and the prepared high temperature resistant, oxidation resistant and wear resistant coating powder was used to prepare the laser cladding coating on the surface of the metal substrate by synchronous powder feeding. The laser power was 700 W, the spot diameter was 2 mm, the powder feeding speed was 10 g / min, the scanning speed was 1 mm / s, the overlap rate was 35%, and the high purity argon gas flow rate was 1 L / min. The prepared phase composition was WC+Co+hBN+W2Co 21 Coating composed of TiHfTaB with B6+BCC structure; (5) Precision rolling of coating: The coating surface was rolled using a single crystal diamond ball head tool. The machine speed was 200 r / min, the feed rate was 0.01 mm / r, the curvature radius of the diamond ball head was 1.0 mm, and the angle between the axis of the diamond indenter and the normal of the coating surface was 45°. A plastic deformation layer with a thickness of 16 μm was formed on the surface of the coating. The dislocation density in the plastic deformation layer was 9.4×10 8 mm -2 , porosity 0.08%, the phase of the plastic layer remains unchanged; (6) Aging heat treatment of the coating: The rolled coating was heated to 700 °C in a vacuum at a heating rate of 5 °C / min and an initial vacuum of 5 Pa. After being kept at this temperature for 3 h, the coating was cooled in the furnace. Short-range ordered Ti-B, Hf-B, and Ta-B complexes with a size of 2 nm were formed in the TiHfTaB in the plastic deformation layer on the coating surface, and the B atoms were located in the tetrahedral gaps of the TiHfTaB lattice.

[0013] Example 2: A method for preparing a protective coating material for gas turbine components: The composition of the protective coating material for gas turbine components is 8% by weight of boron-doped TiHfTa medium entropy alloy, 7% by weight of Co, and the rest by weight of WC; the molar ratio of Ti:Hf:Ta in the boron-doped TiHfTa medium entropy alloy is 1:1:1, and the boron content is 0.9at.%; the coating phase composition is WC+Co+hBN+W2Co 21 TiHfTaB with B6+BCC structure has a 26μm plastic deformation layer on its surface. In the plastic deformation layer, there are short-range ordered Ti-B, Hf-B, and Ta-B complexes with a size of 4nm in TiHfTaB, and the B atoms are in the tetrahedral gaps of the TiHfTaB lattice.

[0014] The preparation method of the protective coating material for gas turbine components is as follows: (1) Preparation of boron-doped TiHfTa medium-entropy alloy powder: Ti, Hf and Ta powders were weighed in a molar ratio of 1:1:1 and put into a planetary ball mill for 96 h. After filtering and spray drying, spherical powders with a particle size of 27 μm were obtained. The spherical powders were pressed into green bodies with a thickness of 1 mm and a density of 55%. First, a boronizing medium was loaded into a ceramic crucible with a lid. The composition of the boronizing medium was 15 wt.%, 17 wt.% of B4C, 17 wt.% of KBF4, 6 wt.% of LaF3, and the rest was SiC. The weight ratio of the boronizing medium to the green body was 4:1. After the green body was buried, the thickness of the boronizing agent filled between the crucible wall was 6 mm. The mixture was kept at 1000 °C in an argon atmosphere for 3 h. After crushing and sieving, TiHfTa medium-entropy alloy powder containing 0.9 at.% boron was prepared. (2) Preparation of hBN dispersion: Nano-hBN and Tween 80 were added to anhydrous ethanol to form a mixed solution, in which nano-hBN accounted for 2 mol / L and Tween 80 accounted for 0.4 mol / L. After ultrasonic dispersion treatment for 50 min, the pH value was adjusted to 9 with ammonia water and the Zeta potential was 38 mV, thus preparing the hBN dispersion. (3) Preparation of protective coating powder: Weigh the raw material powder according to weight percentage, wherein the entropy alloy powder accounts for 8%, Co accounts for 7%, and the rest is WC powder in the boron-doped TiHfTa; ball mill the weighed raw material powder for 20 hours, filter and spray dry it, and then vacuum sinter it at 1200℃ for 2 hours to prepare porous spherical composite powder; immerse the spherical composite powder in hBN dispersion system, the molar ratio of hBN to Co in the spherical composite powder is 1.7:10, and put it into a vacuum drying oven for vacuum adsorption and drying treatment, the vacuum degree is 190Pa, and the vacuum adsorption and drying treatment is first kept at 60℃ for 1.5 hours, and then dried at 115℃ for 2.5 hours, so that the composite sol is completely adsorbed into the pores of the agglomerate, and a protective coating powder is prepared, the average particle size is 41μm, and its composition is WC+Co+hBN+BCC structure TiHfTaB; (4) Laser cladding coating preparation: The metal substrate was kept at 120°C for 50 min, and the prepared high temperature resistant, oxidation resistant and wear resistant coating powder was used to prepare the laser cladding coating on the surface of the metal substrate by synchronous powder feeding. The laser power was 900 W, the spot diameter was 4 mm, the powder feeding speed was 15 g / min, the scanning speed was 2 mm / s, the overlap rate was 40%, and the high purity argon gas flow rate was 2 L / min. The prepared phase composition was WC+Co+hBN+W2Co 21 Coating composed of TiHfTaB with B6+BCC structure; (5) Precision rolling of coating: The coating surface was rolled using a single crystal diamond ball head tool. The machine speed was 300 r / min, the feed rate was 0.02 mm / r, the curvature radius of the diamond ball head was 1.0 mm, and the angle between the axis of the diamond indenter and the normal of the coating surface was 45°. A plastic deformation layer with a thickness of 26 μm was formed on the surface of the coating. The dislocation density in the plastic deformation layer was 1.7×10 9 mm -2 , porosity 0.06%, the phase of the plastic layer remains unchanged; (6) Aging heat treatment of the coating: The rolled coating was heated to 780 °C in a vacuum at a heating rate of 5 °C / min and an initial vacuum of 8 Pa. After being kept at this temperature for 4 h, it was cooled in the furnace. Short-range ordered Ti-B, Hf-B, and Ta-B complexes with a size of 4 nm were formed in the TiHfTaB in the plastic deformation layer on the coating surface, and the B atoms were located in the tetrahedral gaps of the TiHfTaB lattice.

Claims

1. A gas turbine component protective coating material, characterized in that The composition is 4-10% boron-doped TiHfTa medium entropy alloy, 5-10% Co, and the rest is WC by weight percentage; the molar ratio of Ti:Hf:Ta in the boron-doped TiHfTa medium entropy alloy is 1:1:1, and the boron content is 0.5-1.0 at.%; the coating phase composition is WC+Co+hBN+W2Co 21 TiHfTaB with B6+BCC structure has a 15~30μm plastic deformation layer on its surface. In the plastic deformation layer, there are short-range ordered Ti-B, Hf-B, and Ta-B complexes with a size of 1~5nm in TiHfTaB, and the B atoms are in the tetrahedral gaps of the TiHfTaB lattice.

2. A method for preparing a protective coating material for gas turbine components, characterized in that The following steps are included in sequence: (1) Preparation of boron-doped TiHfTa medium-entropy alloy powder: Ti, Hf and Ta powders were weighed in a molar ratio of 1:1:1 and put into a planetary ball mill for 72-96 h. After filtering and spray drying, spherical powders with a particle size of 20-30 μm were obtained. The spherical powders were pressed into green bodies with a thickness of 0.5-1 mm and a density of 52-56%. The boron-containing medium was first loaded into a ceramic crucible with a lid. The composition of the boron-containing medium was 10-20 wt.% of B4C, 10-20 wt.% of KBF4, 5-10 wt.% of LaF3, and the rest was SiC. The mixture was kept at 900-1000 °C in an argon atmosphere for 2-3 h. After crushing and sieving, TiHfTa medium-entropy alloy powders with a boron content of 0.5-1.0 at.% were prepared. (2) Preparation of hBN dispersion: Nano-hBN and Tween 80 were added to anhydrous ethanol to form a mixed solution, in which nano-hBN accounted for 1-2 mol / L and Tween 80 accounted for 0.1-0.5 mol / L. After ultrasonic dispersion and pH adjustment, the Zeta potential was adjusted to 30-40 mV, and the hBN dispersion was prepared. (3) Preparation of protective coating powder: Weigh raw material powders by weight, wherein entropy alloy powder accounts for 4-10% of boron-doped TiHfTa, Co accounts for 5-10%, and the rest is WC powder; ball-mill the weighed raw material powders for 10-20 hours, filter and spray-dry, and then vacuum sinter at 1150-1250°C for 1-2 hours to prepare porous spherical composite powders; immerse the spherical composite powders in a hBN dispersion system, wherein the molar ratio of hBN to Co in the spherical composite powders is (1-2):10, and place the spherical composite powders in a vacuum drying oven for vacuum adsorption and drying treatment, with a vacuum degree of ≤200Pa, so that the composite sol is completely adsorbed into the pores of the agglomerates, to prepare protective coating powders with an average particle size of 30-45 μm and a composition of WC+Co+hBN+BCC structured TiHfTaB; (4) Preparation of coating by laser cladding: The metal substrate is kept at 100-150°C for 30-60 min, and the prepared high temperature resistant, oxidation resistant and wear resistant coating powder is used to prepare the laser cladding coating on the surface of the metal substrate by synchronous powder feeding. The laser power is 600-1000 W, the spot diameter is 2-4 mm, the powder feeding speed is 10-15 g / min, the scanning speed is 1-3 mm / s, and the overlap rate is 30-40%. The prepared phase composition is WC+Co+hBN+W2Co 21 Coating composed of TiHfTaB with B6+BCC structure; (5) Precision rolling of coating: The coating surface is rolled using a single crystal diamond ball head tool. The machine speed is 200-300 r / min, the feed rate is 0.01-0.04 mm / r, the curvature radius of the diamond ball head is 1.0 mm, and a plastic deformation layer with a thickness of 15-30 μm is formed on the surface of the coating. The dislocation density in the plastic deformation layer is 6×10 8 ~3×10 9 mm -2 , porosity 0.05~0.1%, the phase of the plastic layer remains unchanged; (6) Aging heat treatment of the coating: The rolled coating is heated to 700-780°C in a vacuum, kept at this temperature for 3-5 hours, and then cooled in the furnace. Short-range ordered Ti-B, Hf-B, and Ta-B complexes with a size of 1-5 nm are formed in the TiHfTaB in the plastic deformation layer on the coating surface, and the B atoms are located in the tetrahedral gaps of the TiHfTaB lattice.

3. The method for preparing a gas turbine component protective coating material according to claim 2, further characterized by: (1) When preparing boron-doped TiHfTa medium entropy alloy powder, the weight ratio of the boronizing medium to the green body is 4:1, and the thickness of the boronizing agent filled between the green body and the crucible wall after the green body is buried is greater than 4 mm; (2) When preparing the hBN dispersion system, after ultrasonic dispersion treatment for 30-60 min, the pH value was adjusted to 8-9 with ammonia water; (3) When preparing high temperature resistant, oxidation resistant and wear resistant coating powder, the vacuum adsorption and drying process is first kept at 50~60℃ for 1~2h, and then dried at 110~120℃ for 2~3h; (4) When laser cladding is used to prepare the coating, the flow rate of high-purity argon gas is 1~2L / min; (5) During precision rolling of the coating, the angle between the axis of the diamond indenter and the normal of the coating surface is 45°; (6) During the aging heat treatment of the coating, the heating rate is 5°C / min and the initial vacuum degree is 5~10Pa.

Citation Information

Patent Citations

  • Laser hard-surface coating process method of titanium alloy vane of gas turbine

    CN101613860A

  • Composite WC-CrC-CoCr thermal spraying powder and preparation method and application thereof

    CN112760540A

Cited By

  • Method for preparing carbon-carbon heater by asphalt impregnation method

    CN121342537A